Structural self-organization of solid-state products during interaction of halogenated compounds with bulk Ni-Cr alloy; Materials Letters; Vol. 179 - Kenzhin R. M.; Bauman Yu. I.; Volodin A. M.; Mishakov I. V. Iljya Vladimirovich; Vedyagin A. A. Aleksey Anatolievich (2016, 2016)
Title screen